Adverse effects of small for gestational age differ by gestational week among very preterm infants. Issue 2 (5th May 2018) - Jensen, Erik A; Foglia, Elizabeth E; Dysart, Kevin C; Simmons, Rebecca A; Aghai, Zubair H; Cook, Alison; Greenspan, Jay S; DeMauro, Sara B
Abstract : Objective: To characterise the excess risk for death, grade 3–4 intraventricular haemorrhage (IVH), bronchopulmonary dysplasia (BPD) and stage 3–5 retinopathy of prematurity independently associated with birth small for gestational age (SGA) among very preterm infants, stratified by completed weeks of gestation. Methods: Retrospective cohort study using the Optum Neonatal Database. Study infants were born <32 weeks gestation without severe congenital anomalies. SGA was defined as a birth weight <10th percentile. The excess outcome risk independently associated with SGA birth among SGA babies was assessed using adjusted risk differences (aRDs). Results: Of 6708 infants sampled from 717 US hospitals, 743 (11.1%) were SGA. SGA compared with non-SGA infants experienced higher unadjusted rates of each study outcome except grade 3–4 IVH among survivors. The excess risk independently associated with SGA birth varied by outcome and gestational age. The highest aRD for death (0.27; 95% CI 0.13 to 0.40) occurred among infants born at 24 weeks gestation and declined as gestational age increased. In contrast, the peak aRDs for BPD among survivors (0.32; 95% CI 0.20 to 0.44) and the composites of death or BPD (0.35; 95% CI 0.24 to 0.46) and death or major morbidity (0.35; 95% CI 0.24 to 0.45) occurred at 27 weeks gestation. The risk-adjusted probability of dying or developing one or more of the evaluated morbidities among SGA infants was similar to that of non-SGA infants born approximately 2–3 weeks less mature. Conclusion: The excess risk for neonatal morbidity and mortality associated with being born SGA varies by adverse outcome and gestational age.